Brain network integration dynamics are associated with loss and recovery of consciousness induced by sevoflurane. Issue 9 (19th March 2021) - Luppi, Andrea I.; Golkowski, Daniel; Ranft, Andreas; Ilg, Rüdiger; Jordan, Denis; Menon, David K.; Stamatakis, Emmanuel A.
Abstract: The dynamic interplay of integration and segregation in the brain is at the core of leading theoretical accounts of consciousness. The human brain dynamically alternates between a sub‐state where integration predominates, and a predominantly segregated sub‐state, with different roles in supporting cognition and behaviour. Here, we combine graph theory and dynamic functional connectivity to compare resting‐state functional MRI data from healthy volunteers before, during, and after loss of responsiveness induced with different concentrations of the inhalational anaesthetic, sevoflurane. We show that dynamic states characterised by high brain integration are especially vulnerable to general anaesthesia, exhibiting attenuated complexity and diminished small‐world character. Crucially, these effects are reversed upon recovery, demonstrating their association with consciousness. Higher doses of sevoflurane (3% vol and burst‐suppression) also compromise the temporal balance of integration and segregation in the human brain. Additionally, we demonstrate that reduced anticorrelations between the brain's default mode and executive control networks dynamically reconfigure depending on the brain's state of integration or segregation. Taken together, our results demonstrate that the integrated sub‐state of brain connectivity is especially vulnerable to anaesthesia, in terms of both its complexity and information capacity, whose breakdown represents a generalisable biomarker of loss of consciousness and its recovery. Abstract : We use functional MRI to study the effects of sevoflurane anaesthesia on the dynamics of integration and segregation in the human brain. We show that brain states characterised by high integration are especially vulnerable to general anaesthesia, in terms of both complexity and information capacity. Higher doses of sevoflurane also compromise the temporal balance of integration and segregation in the human brain.